- #1

- 45

- 0

Thanks in advance.

- Thread starter ssj5harsh
- Start date

- #1

- 45

- 0

Thanks in advance.

- #2

HallsofIvy

Science Advisor

Homework Helper

- 41,833

- 956

- #3

- 2

- 0

i was looking for the same thing today and came across this question

what i came up with was a combination of 8 functions for a 3d representation, although i am not certain if they are correct. also of note is that this is for it laying on its side. anyway, here goes:

x = y^{3} + z^{3} + 1, For x, 0 to h

-x = y^{3} + z^{3} + 1, For x, -h to 0

-x = -y^{3} + z^{3} + 1, For x, -h to 0 (?)

x = -y^{3} + z^{3} + 1, For x, 0 to h (?)

x = y^{3} + z^{3} - 1, For x, -h to 0

-x = y^{3} + z^{3} - 1, For x, 0 to h

-x = -y^{3} + z^{3} - 1, For x, 0 to h (?)

x = -y^{3} + z^{3} - 1, For x, -h to 0 (?)

where 2h = height of hourglass

from here it (should) should just be a matter of scaling, choosing of sand, and experimental trial and error to come up with the correct amount of the particularly chosen sand.

again, am not sure if this is correct. . . .

Best Regards,

what i came up with was a combination of 8 functions for a 3d representation, although i am not certain if they are correct. also of note is that this is for it laying on its side. anyway, here goes:

x = y

-x = y

-x = -y

x = -y

x = y

-x = y

-x = -y

x = -y

where 2h = height of hourglass

from here it (should) should just be a matter of scaling, choosing of sand, and experimental trial and error to come up with the correct amount of the particularly chosen sand.

again, am not sure if this is correct. . . .

Best Regards,

Last edited:

- #4

- 2

- 0

whoops, let's try this again. . . .

f(y,z) = n(y^{3} + z^{3}) + a; For y = 0, and positive y; For x, 0 to h

f(y,z) = n(-y^{3} - z^{3}) - a; For negative y; For x, -h to 0

f(y,z) = n(y^{3} - z^{3}) - a; For negative y; For x, -h to 0

f(y,z) = n(-y^{3} + z^{3}) + a; For y = 0, and positive y; For x, 0 to h

f(y,z) = n(y^{3} + z^{3}) - a; For negative y; For x, 0 to h

f(y,z) = n(-y^{3} - z^{3}) + a; For y = 0, and positive y; For x, -h to 0

f(y,z) = n(y^{3} - z^{3}) + a; For y = 0, and positive y; For x, -h to 0

f(y,z) = n(-y^{3} + z^{3}) - a; For negative y; For x, 0 to h

where h = 1/2 hourglass height,

a = the cubed root of the hourglass annulous radius,

and

n = a height to width coefficient

f(y,z) = n(y

f(y,z) = n(-y

f(y,z) = n(y

f(y,z) = n(-y

f(y,z) = n(y

f(y,z) = n(-y

f(y,z) = n(y

f(y,z) = n(-y

where h = 1/2 hourglass height,

a = the cubed root of the hourglass annulous radius,

and

n = a height to width coefficient

Last edited:

- Replies
- 1

- Views
- 621

- Last Post

- Replies
- 1

- Views
- 1K

- Last Post

- Replies
- 1

- Views
- 655

- Last Post

- Replies
- 5

- Views
- 2K

- Last Post

- Replies
- 8

- Views
- 3K

- Last Post

- Replies
- 1

- Views
- 6K

- Last Post

- Replies
- 18

- Views
- 3K

- Last Post

- Replies
- 2

- Views
- 1K

- Last Post

- Replies
- 1

- Views
- 2K

- Last Post

- Replies
- 2

- Views
- 5K